Nucleic acid approaches to toxin detection - Chatwell, Nicola (2013)
PCR is commonly used for detecting contamination of foods by toxigenic bacteria. However, it is unknown whether it is suitable for detecting toxins in samples which are unlikely to contain bacterial cells, such as purified biological weapons. Quantitative real-time PCR assays were developed for amplification of the genes encoding Clostridium botulinum neurotoxins A to F, Staphylococcal enteroxin B (SEB), ricin, and C. perfringens alpha toxin. Botulinum neurotoxins, alpha toxin, ricin and V antigen from Yersinia pestis were purified at Dstl using methods including precipitation, ion exchange, FPLC, affinity chromatography and gel filtration. Additionally, toxin samples of unknown purity were purchased from a commercial supplier. Q-PCR analysis showed that DNA was present in crudely prepared toxin samples. However, the majority of purified or commercially produced toxins were not detectable by PCR. Therefore, it is unlikely that PCR will serve as a primary toxin detection method in future.